Information Technology, Strategic Innovation, and Customer Relationships in Indonesian IT Startups - Hidayat, Ravindra Safitra; Riyadi, Selamet; Mudjijah, Slamet; Maulana, Panca; Nugroho, Heru (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to explore the dynamic interaction between information technology, strategic innovation, and customer relationship management in Indonesian IT startups. Amid the rapid expansion of the digital economy and the increasing demand for digital services, startups in Indonesia face opportunities and challenges in leveraging technology to enhance customer engagement. This research employs a qualitative research design with semi-structured interviews and thematic analysis, investigating how these startups navigate a resource-constrained environment to adopt digital tools, drive innovation, and build sustainable customer relationships. This study aims to explore the dynamic interaction between information technology, strategic innovation, and customer relationship management in Indonesian IT startups. Amid the rapid expansion of the digital economy and the increasing demand for digital services, startups in Indonesia face opportunities and challenges in leveraging technology to enhance customer engagement. This research employs a qualitative research design with semi-structured interviews and thematic analysis, investigating how these startups navigate a resource-constrained environment to adopt digital tools, drive innovation, and build sustainable customer relationships.